Effect of expertise on butterfly stroke coordination - Seifert, L.; Delignieres, D.; Boulesteix, L.; Chollet, D. (Journal of Sports Sciences, 2006)
The aim of this study was to compare the arm to leg coordination in the butterfly stroke among three groups of male swimmers with different skill levels (10 elite, 10 non-elite and 10 young rising swimmers) at four race paces (400-m, 200-m, 100-m and 50-m). Using a qualitative video analysis and a hip velocity-video system (50 Hz), key events of the arm and leg movement cycle were defined and four point estimates of relative phase (RP1, RP2, RP3, RP4) assessed the arm to leg coordination between the propulsive (pull and push of arms and downward movement of leg undulation) and non-propulsive times (entry, catch and recovery of arms and upward of leg undulation). The relative phase was based on the time difference between: entry of the hands in the water and high break point of the first undulation for RP1; beginning of the hands` backward movement and low break point of the first undulation for RP2; hands` arrival in a vertical plane to the shoulders and high break point of the second undulation fro RP3; hands` release from the water and low break point of the second undulation for RP4. With increased velocity, stroke rate and/or expertise, the swimmers increased the synchronization between the arm and leg key points. On the mean swimmer groups, the RP1 get closer to in-phase coordination mode (from 11.6 to 0.5°), while RP2 switched from antiphase (186.5°) to 226.7° out-of-phase when velocity and stroke rate increased. On the mean of the four paces, RP1 and RP4 showed a closer in-phase coupling between arm and leg with increased skill level, while RP3 was in out-of-phase for the two less expert groups (316.2° and 312.8°) and was closed to an in-phase mode for the elite swimmers (333.3°). The RP2 also changed from anti-phase (187°) to 225.6° out-of-phase with increased expertise. Finally, these changes led to a higher continuity between the propulsive actions, which is propitious to improving the swim velocity, suggesting that coaches and swimmers should monitor arm to leg coordination.